Utilization of Mobile Technology for Nearest Tourist Destination Recommendations in Sleman Regency Using the Haversine Formula - Akmal Faizy; Joko Sutopo (Kirana Publisher (KNPub), 2024)
The tourism sector in Sleman Regency, Yogyakarta, experiences a high volume of visitors, especially to cultural and natural attractions. However, the current systems for finding and navigating tourist destinations rely on manual search processes and lack integration, leading to suboptimal user experiences. This study aims to address these limitations by developing a mobile-based tourist destination recommendation system that provides an efficient, categorized, and navigable user experience. The system categorizes destinations into four main type that is nature, temple, family, and education, and users to explore locations based on their preferences. By employing the Haversine formula, the system recommends destinations based on proximity. Additionally, users can purchase tickets directly through the app, enhancing convenience, while a bug reporting feature enables continuous improvement based on user feedback. This integration of interactive and practical features aims to improve visitor satisfaction and streamline the tourism experience in Sleman Regency, contributing positively to the local tourism industry. The system operates with three main user roles that are Tourist, Tourist Admin, and Superadmin.